Covalent organic frameworks and organic cage structures - Banerjee, Rahul; Champness, Neil R. (Royal Society of Chemistry, 2017)
The last 20 years have seen an enormous interest in research on the topic of crystalline porous framework materials, especially metal–organic frameworks (MOFs). MOFs exploit reversible metal–coordination chemistry to create extended, crystalline solids.1 However, a similar set of porous ordered covalent networks based on the reversible and modular connection of a vast array of rigid and symmetrical building blocks through covalent bonds has also emerged during this time. These materials, coined as “Covalent Organic Frameworks (COFs)”, have summoned considerable attention in the last decade, starting with a significant contribution from the Yaghi group,2 owing to their unique designing features as well as enormous potential.3 Like COFs, porous molecular crystals that are not interconnected by covalent bonding have also picked up significant research interest. Although these materials do resemble COFs, unlike COFs, they can be solution processable.4 For any structural chemists, these materials are excellent tools that can lead to more informed design processes and create a deeper understanding of how targeted porous extended structures should be made.